Interoperability framework for integrated e-health services - M. Miftakul Amin; Adi Sutrisman; Deris Stiawan; Ermatita Ermatita; Mohammed Y. Alzahrani; Rahmat Budiarto (Institute of Advanced Engineering and Science, 2020)
As one of the country with largest population in the world, Indonesia is facing major challenge to serve people in various sectors, one of them is health sector. Utilization of Information and Communication Technology (ICT) has a strategic role in improving efficiency and expanding services access. The main challenge related to data interoperability is the ability to integrate and synchronize data sourced from health information (e-health) systems with different (heterogeneous) platforms. This research aims to build a framework to materialize data interoperability and information exchange among e-health systems. The interoperability is materialized by utilizing service oriented architecture (SOA) paradigm and is implemented using Web Service technology. Service oriented analysis and design (SOAD) is used as method in the system development at the analysis phase and designing phase to generate service portfolio which consisting of three levels: conceptual view, logical view, and physical view. This research intruduces Interoperability Matrix (IM) to describe the modules and entities that involved in the framework design. The framework resulted from this research can be used as reference in e-health systems development in variety of health care applications.